Multi-phasic life-threatening anaphylaxis refractory to epinephrine managed by extracorporeal membrane oxygenation (ECMO): A case report - Grafeneder, Juergen; Ettl, Florian; Warenits, Alexandra-Maria; Buchtele, Nina; Lobmeyr, Elisabeth; Staudinger, Thomas; Schwameis, Michael; Sperr, Wolfgang R.; Gelbenegger, Georg; Schoergenhofer, Christian; Jilma, Bernd (Frontiers in Allergy, 2022)
We present a case of a 52-year-old patient suffering from multi-phasic life-threatening anaphylaxis refractory to epinephrine treatment. Extracorporeal membrane oxygenation (ECMO) therapy was initiated as the ultima ratio to stabilize the patient hemodynamically during episodic severe bronchospasm. ECMO treatment was successfully weaned after 4 days. Mastocytosis was diagnosed as the underlying condition. Although epinephrine is recommended as a first-line treatment for anaphylaxis, this impressive case provides clear evidence of its limited therapeutic success and emphasizes the need for causal therapies.